2017
DOI: 10.1177/2048872617719650
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of distinctive clinical and cardiac magnetic resonance features between ST elevation myocardial infarction patients with incomplete myocardial rupture and those with moderate to severe pericardial effusion

Abstract: IMR is generally silent and occurs in younger patients with smaller infarct size than those with PE although both present late and are often untreated with reperfusion therapy. These findings may warrant imaging assessment in ST elevation myocardial infarction patients with delayed admission, particularly in absence of reperfusion, to rule out an IMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…However, it has brought a new challenge-myocardial ischemia/reperfusion injury (IRI) leading to microvascular obstruction (MVO) and intramyocardial hemorrhage (IMH) [18] . Moreover, a recent study revealed that patients with impending CR had increased occurrence of IMH and MVO compared with controls [19] . Regarding risk factors for CR in the PCI era, it may be necessary to focus on IRI.…”
Section: Discussionmentioning
confidence: 97%
“…However, it has brought a new challenge-myocardial ischemia/reperfusion injury (IRI) leading to microvascular obstruction (MVO) and intramyocardial hemorrhage (IMH) [18] . Moreover, a recent study revealed that patients with impending CR had increased occurrence of IMH and MVO compared with controls [19] . Regarding risk factors for CR in the PCI era, it may be necessary to focus on IRI.…”
Section: Discussionmentioning
confidence: 97%
“…Наиболее информативные методы диагностики разрыва миокарда включают в себя левую вентрикулографию, трансторакальную ЭхоКГ [3]; компьютерную томографию [4]. В нашем случае наиболее доступным методом диагностики разрыва миокарда была ЭхоКГ, по данным которой был найден сам разрыв и обнаружено наличие гемоперикарда.…”
Section: Discussionunclassified
“…A clinical study compared the clinical, angiographic and CMR characteristics of patients with AMI complicated by an incomplete myocardial rupture (IMR) or a moderate-severe pericardial effusion. 7 IMR is generally silent and occurs in younger patients with smaller infarct size than those with pericardial effusion. Both groups of patients present late and are often untreated with reperfusion therapy.…”
mentioning
confidence: 99%